Occurrence of common mental disorders among former elite athletes - Marija Ivanović; Draženka Mačak (Exercise and Quality of Life)
Participating in elite sports can be beneficial for many reasons – but the question arises: what is the payoff to be an elite athlete or what are the consequences of being an elite athlete in sports? The phenomenon which became popular and opens many conversations in sport and psychology circles is the occurrence of common mental disorders (CMD) in former elite athletes. In this literature review, three electronic databases were searched: PubMed, Web of Science, ScienceDirect. This paper summarizes eight studies which were selected following the PRISMA guidelines. The studies covered mental health disorders among former elite athletes and their symptoms: distress, sleep disturbance, anxiety/depression, and alcohol misuse, the occurrence of life events and career dissatisfaction. This literature review showed the prevalence of CMD in former elite athletes. There were no results about the contribution to developing CMD in former elite athletes. Factors associated with the occurrence of CMD in former athletes included involuntary retirement from the sport, concussions, collision/high contact sport, increased body mass index, osteoarthritis.